EFEK RESIDU KOMPOS TANDAN KOSONG KEPLAPA SAWIT SETELAH PENANAMAN KEDELAI EDAMAME TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - Joni Adri; Fetmi Silvina; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research entitled Residual effects of Empty Palm Bunches compost (EPB) after planting edamame soybean on growth and production of onion (Allium ascalonicum L.). This research aims to determine the residual effects of EPB compost on growth and production of onion (Allium ascalonicumL.). This research use completely randomized design (CRD) which consists 4 treatments that is EPB compost residue with a dose of 5 ton/ha (K1), EPB compost residue with dose of 10 ton/ ha (K2), EPB compost residue with dose of 15 ton/ha (K3) and EPB compost residue with dose of 20 ton/ha (K4) that each treatment consisted 4 replications, then obtain 16 units of trial. Parameters measured were the number of leaves per clump, the number of tubers per clump, tuber fresh weight per clump, circumference of tubers, plant dry weight and shelf tubers dry weight. The results show that the residual effects of the EPB compost treatment after planting edamame soybean significantly affected on number of leaves per clump, the number of tubers per clump, tuber fresh weight per clump, circumference of tubers, plant dry weight and shelf tubers dry weight of onion. The best growth and production of onion obtained by usage of EPB compost residue with dose of 20 ton/ha. Keywords: Empty Palm Bunches compost, residues, onion